(untitled) (Politeja, 2017)
Religious education in school in Poland – analysis of selected media debates The aim of this article is to present an analysis of media debates on religious education in a public schools, conducted in polish opinion‑forming newspapers. In the spring 2015 citizen’s initiative “Secular school” initiated changes in a law which allowed to finance religion lessons from public funds. The author tackles a topic from the perspective of the presence of religious education in schools for 25 years. Such approach gives opportunity to confront contemporary views on this issue, presented over the past year in the media, with public opinion research on this subject, conducted since 1990.